2020
DOI: 10.2147/oarrr.s270700
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Outcomes of Patients with Rheumatoid Arthritis Treated in a Disease Management Program: Real-World Results</p>

Abstract: Background: Care models can affect the clinical outcome of patients with rheumatic and musculoskeletal diseases. Objective: We aimed to compare how an innovative model of a rheumatoid arthritis disease-management program can improve the clinical outcomes of patients compared to a conventional assessment approach. Methods: We performed a retrospective analysis of real-world data from clinical records of a cohort of 5078 patients diagnosed with rheumatoid arthritis who were followed up at the Center of Excellenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 31 publications
2
13
1
Order By: Relevance
“…A well-known fact is that middle to older-aged individuals with female predominance are the most frequent patient group affected by RA. Our findings were comparable to these well-established features of RA [ 3 , 5 , 11 , 17 , 25 , 26 ]. Ageing is essential for developing higher risks and hospitalizations associated with comorbidities [ 25 , 27 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A well-known fact is that middle to older-aged individuals with female predominance are the most frequent patient group affected by RA. Our findings were comparable to these well-established features of RA [ 3 , 5 , 11 , 17 , 25 , 26 ]. Ageing is essential for developing higher risks and hospitalizations associated with comorbidities [ 25 , 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings were comparable to these well-established features of RA [ 3 , 5 , 11 , 17 , 25 , 26 ]. Ageing is essential for developing higher risks and hospitalizations associated with comorbidities [ 25 , 27 ]. The mean age of the patients and the distribution of the comorbid diseases in each group were similar in the current study as Bawazir’s study [ 17 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…[17][18][19][20][21] Furthermore, the increase in the remission rates over time that we observed is still considered quite inadequate. 10,[22][23][24][25] Explanations that come to mind include our patient's low accessibility to b/ts-DMARDs, their relative long disease duration, 26 and/or a delay in the implementation of an adequate tight control strategy. In addition, the use of the SDAI in our cohort, stricter in comparison with the 28-joint count disease activity score, 27 which has been used in the majority of RA LA cohorts published (see supplementary table), could partially explain the low remission rates we observed in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, patients cared for at this center exhibited lower levels of disease activity, a high proportion of them were classified as being in remission while a low proportion exhibited high disease activity. 4 In Chicago, Arora et al 3 compared the care received by SLE patients in two settings-a Lupus Clinic (LC) and a General Rheumatology Clinic (GRC) within the same academic institution. They showed that care provided at the LC or who were seen by rheumatologists with a high volume of SLE patients provided a better quality of care (including sunscreen and drug counseling, vaccination, use of steroid-sparing agents, cardiovascular disease risk assessment, among others) than the one provided at the GRC.…”
Section: Introductionmentioning
confidence: 99%